Perbedaan Pencapaian Kompetensi Mahasiswa Ners (Komunikasi, Keterampilan dan Perilaku Profesional) Antara Stase Keperawatan Anak Dengan Keperawatan Maternitas Sesudah Intervensi Metode Bimbingan One Minute Preceptor (OMP) pada Preceptor di Kota Bengkulu - Emi Pebriani; Yulastri Arif; Mira Susanti (Universitas Batanghari Jambi, 2021)
Professional nurse competence is measured through a competency test conducted by the Ministry of Research, Technology and Higher Education (Kemenristek Dikti, 2015). The evaluation results obtained show that from year to year the graduation rate fluctuates. In 2016 the graduation rate was 53.46%, in 2017 the graduation rate was 50.58%, in 2018 the graduation rate was 50.38% and in 2019 the graduation rate for ukom was 64.6% (Kemenristek Dikti, 2019). The data above shows that the national pass rate for the nurse competency test still needs to be improved. This study aims to compare the effectiveness of the One Minute Preceptor (OMP) guidance method on the competency of the stage of Child Nursing and Maternity Nursing in Nursing Profession Students at Dehasen University, Bengkulu City. This type of research is the type of this research is quantitative with a quasi experimental design post test only design. The sample in this research was 30 students. Sampling with total sampling. The mean post-test scores for knowledge, attitudes, skills and cumulative preceptors were higher than the pre-test scores. The average achievement of the communication scores, skills and professional behavior of the students in the maternity nursing stage was higher than that of the children in the nursing stage. There are differences in the achievement of student competencies (communication, skills and professional behavior) between the stage of child nursing and maternity nursing after the intervention of the One Minute Preceptor (OMP) guidance method on the preceptor. It is expected that the preceptor can apply the One Minute Preceptor (OMP) guidance method to every student who is carrying out his practice.